Enhancing balance in Parkinson’s disease patients - Ponebšek, Ana (Annales kinesiologiae (Koper), 2023)
Various physiotherapeutic methods and approaches play a significant role in the treatment of patients with Parkinson’s disease, including the use of enriched environ-ments. Virtual reality (VR) as a type of enriched environment has the potential to create multiple sensory experiences and feedback, influencing various aspects of the patient’s information processing and response. The suitability for home use and the consider-able impact on motivation highlight its advantages over alternative approaches. The objective of this review is to investigate the impact of VR-based exercise on balance outcomes among individuals with Parkinson’s disease. The inclusion criteria consisted of randomized controlled trials (RCTs) that examined the effects of exercise in a VR environment on individuals’ static and dynamic balance outcomes. In order to gather relevant studies, we conducted a comprehensive search across three databases. From a dataset of 625 records, we conducted a comprehensive full-text screening based on spe-cific inclusion and exclusion criteria. This process resulted in the inclusion of 14 RCTs in our review. The emerging evidence regarding exercising in a VR environment does not definitively prove its superiority over standard exercise routines. However, studies have demonstrated that both the experimental and control groups showed compara-ble improvements in enhancing static and dynamic balance among individuals with Parkinson’s disease. The comparable improvements in balance observed between the experimental and control groups signify the potential effectiveness of VR-based exer-cises. This underscores the encouragement for further development in this technology, particularly focusing on fully immersive VR environments, which may yield superior effects in enhancing balance among individuals with Parkinson’s disease.
Keywords: balance; Medicinska rehabilitacija; navidezna resničnost; Parkinsonova bolezen; Parkinson's disease; ravnotežje; rehabilitacija; rehabilitation; virtual reality